Sharia-Compliant Digital Marketing Strategies to Boost Sales Revenue for Micro, Small, and Medium Enterprises in Parepare City - Asih, Nur; Nurhayati, St.; Zubair, Muhammad Kamal; Semaun, Syahriah; Damirah, Damirah (Jurnal Ar-Ribh, 2024)
This study investigates the implementation of sharia-compliant digital marketing strategies to enhance the sales turnover of Micro, Small, and Medium Enterprises (MSMEs) in Parepare City. Using a qualitative approach with a case study methodology, data were collected through direct observation, in-depth interviews, and documentation. The research focuses on understanding the effectiveness of digital marketing through social media platforms such as Facebook, Instagram, and TikTok while adhering to Islamic ethical principles. The findings reveal that before adopting digital marketing strategies, MSMEs in Parepare City experienced stagnant, declining, or inconsistent turnover due to reliance on traditional marketing methods. However, after utilizing social media for product promotion, most MSMEs reported turnover increases ranging from 20% to 80%. Facebook emerged as the most widely used platform, providing significant outreach and engagement opportunities. Additionally, TikTok and Instagram contributed to customer engagement through creative and interactive content. From an Islamic perspective, the study highlights that MSME actors operate their businesses in line with the principles of falah (worldly and spiritual prosperity), emphasizing transparency, fairness, and ethical practices in their marketing efforts. The adoption of sharia-compliant digital marketing strategies not only enhanced sales performance but also supported sustainable and ethical business operations. This study underscores the potential of digital marketing as a transformative tool for MSMEs, particularly when aligned with Islamic values. Future research could expand the scope by exploring additional sectors or regions to provide a more comprehensive understanding of the impact of digital marketing strategies on business growth.